Agronomic Efficiency of Biosolid as Source of Nitrogen to Banana Plants - Luiz Antonio Junqueira Teixeira; Ronaldo Severiano Berton; Aline Reneé Coscione; Luis Alberto Saes; Marcio Koiti Chiba (Applied and Environmental Soil Science)
Sewage sludge (SS) or biosolid has been studied as source of nutrient for several different plant species. It also contributes to soil fertility recycling organic matter and plant nutrients. This followup work examines a three-year (2001–2004) field experiment designed to evaluate the response of banana plants (Cavendish subgroup) to the application of biosolid as source of nitrogen. The treatments consisted of control (mineral PK, no N), three rates of sludge, and two rates of mineral NPK fertilizer. Plant and soil N concentration, fruit yield, plant height, stem diameter, and foliar endurance index were measured. Fruit yield with mineral fertilization or sludge applications did not differ statistically (P>0.05). Application of biosolid resulted in statistically significant higher agronomic efficiency (P<0.05) in comparison to mineral fertilizers. The concentration of soil mineral nitrogen increased using mineral fertilizer or sludge until 0.80 m after three years of application. The effect of the source of N was smaller than the effect of the rate. Biosolid can be used as source of N for banana growers.